The Importance of Social Support, Positive Identity, and Resilience in the Successful Aging of Older Sexual Minority Men - Henrique Pereira; Patrícia Silva (Geriatrics, 2021)
The aim of this study was to assess the relationship between social support, positive identity, and resilience and the successful aging of older sexual minority men. The study involved having 210 self-identified gay and bisexual men aged between 50 and 80 years complete a cross-sectional online survey comprised of sociodemographic information; the Portuguese version of the Multidimensional Scale of Perceived Social Support; the Lesbian, Gay, and multifactor Bisexual Positive Identity Measure; the Connor–Davidson Resilience Scale 10; and the Successful Aging Perceptions Scale. The results showed that self-identified gay participants showed higher levels of positive identity, while bisexual participants scored higher for resilience, mental health, and successful aging. Higher levels of social support, resilience, and positive identity were significant predictors of mental health (28%), physical health (18%), and successful aging (10%) in our sample. These results offer similarities with the growing body of literature on the positive factors of successful aging in the gay and bisexual men communities, which is an important step in the development of aging and health preventive initiatives among this population.